1991
DOI: 10.1128/mcb.11.4.2081-2095.1991
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA Polymerase a Gene: Sequences Controlling Expression in Cycling and Serum-Stimulated Cells

Abstract: We have investigated the DNA polymerase alpha promoter sequence requirements for the expression of a heterologous gene in actively cycling cells and following serum addition to serum-deprived cells. An 11.4-kb genomic clone that spans the 5' end of this gene and includes 1.62 kb of sequence upstream from the translation start site was isolated. The transcription start site was mapped at 46 +/- 1 nucleotides upstream from the translation start site. The upstream sequence is GC rich and lacks a TATA sequence but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Immunoblot analysis of total cell extracts revealed that, whereas control cells exhibited a marked increase in the expression of E2F-1 as early as 1 h after induction of differentiation, consistent with the fact that the E2F-1 gene is an early-response gene (Johnson et al, 1994), PARP-depleted antisense cells contained negligible amounts of E2F-1 during the 24 h exposure to inducers of differentiation (Figure 8). The induction of both DNA pol R and PCNA in control cells occurred after that of E2F-1, consistent with their being encoded by lateresponse genes (Pearson et al, 1991). These results indicate that PARP may regulate the expression of DNA pol R and PCNA genes during early S-phase indirectly by affecting the expression of the transcriptional factor, E2F-1, which in turn can regulate the transcription of both the DNA pol R and PCNA genes, as well as the E2F-1 gene itself.…”
Section: Effects Of Parp Depletion By Antisense Rna Expression On The...supporting
confidence: 65%
See 2 more Smart Citations
“…Immunoblot analysis of total cell extracts revealed that, whereas control cells exhibited a marked increase in the expression of E2F-1 as early as 1 h after induction of differentiation, consistent with the fact that the E2F-1 gene is an early-response gene (Johnson et al, 1994), PARP-depleted antisense cells contained negligible amounts of E2F-1 during the 24 h exposure to inducers of differentiation (Figure 8). The induction of both DNA pol R and PCNA in control cells occurred after that of E2F-1, consistent with their being encoded by lateresponse genes (Pearson et al, 1991). These results indicate that PARP may regulate the expression of DNA pol R and PCNA genes during early S-phase indirectly by affecting the expression of the transcriptional factor, E2F-1, which in turn can regulate the transcription of both the DNA pol R and PCNA genes, as well as the E2F-1 gene itself.…”
Section: Effects Of Parp Depletion By Antisense Rna Expression On The...supporting
confidence: 65%
“…In response to growth stimulation, expression of genes involved in DNA replication has been shown to increase dramatically at late G 1 (Baserga, 1991;Miyazawa et al, 1993), including PCNA, DNA pol R, and DNA primase genes. In mammalian cells, the transcription factor E2F-1 binds to a specific recognition site (5′-TTTCGCGC) and thereby activates the promoters of several genes that encode proteins required for DNA replication and cell growth, including DNA pol R, dihydrofolate reductase, thymidine kinase, c-MYC, c-MYB, PCNA, cyclin D, and cyclin E (Blake and Azizkhan, 1989;DeGregori et al, 1995;Nevins, 1992;Pearson et al, 1991;Slansky et al, 1993). Transcription of the E2F-1 gene, in turn, is also regulated during the cell cycle (Neuman et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half-site recognition by bZip proteins may be biologically significant. Several GCN4-and AP-1-responsive promoters have binding sites that contain only one-half of the consensus core sequence (37)(38)(39)(40)(41)(42). In addition, binding by the bZip transcription factor CREB to an isolated half-site occurs in a phosphorylation-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…A number of promoters that are responsive to bZip transcription factors contain only a single half-site of their consensus sequence. For example, the his3 gene, the jun proto-oncogene, the HIV-LTR, and the genes for human DNA polymerase R and transforming growth factor β1 (TGF-β1) contain isolated 5′-TGAC-3′ sequences that have been reported to confer responsiveness to GCN4 or AP-1 (37)(38)(39)(40)(41)(42). In addition, upon phosphorylation, the bZip protein CREB binds with high affinity in vivo to a half-site of the cAMP-responsive element (CRE) (43,44).…”
mentioning
confidence: 99%